A non-enzyme cascade amplification strategy for colorimetric assay of disease biomarkers. Issue 65 (14th July 2017) - Li, Jiuxing; Gao, Zhuangqiang; Ye, Haihang; Wan, Shulin; Pierce, Meghan; Tang, Dianping; Xia, Xiaohu
Abstract : A non-enzyme cascade amplification strategy for colorimetric assay of disease biomarkers with substantially enhanced detection sensitivity has been developed. Abstract : A non-enzyme cascade amplification strategy, based on the dissolution of Ag nanoparticles and a Pt nanocube-catalyzed reaction, for colorimetric assay of disease biomarkers was developed. This strategy overcomes the intrinsic limitations of enzymes involved in conventional enzymatic amplification techniques, thanks to the utilization of noble-metal nanostructures with superior properties.